Age-Related Differences in Responses to Thoughts of One’s Own Death: Mortality Salience and Judgments of Moral Transgressions - Maxfield, Molly (2007)
Two experiments explored age differences in response to reminders of death. Terror management research has shown that death reminders lead to increased adherence to and defense of one’s cultural worldview. In Study 1, the effect of mortality salience (MS) on evaluations of moral transgressions made by younger and older adults was compared. Whereas younger adults showed the typical pattern of harsher judgments in response to MS, older adults did not. Study 2 compared younger and older adults’ responses to both the typical MS induction and a more subtle death reminder. Whereas younger adults responded to both MS inductions with harsher evaluations, older adults made significantly less harsh evaluations after the subtle MS induction. Explanations for this developmental shift in responses to reminders of death are discussed.